Relationship Among Inflammation, Overweight Status, and Cognitive Impairment in a Community-Based Population of Chinese Adults - Wang, Jing; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2020)
Purpose: To determine the association between overweight and high-sensitivity C-reactive protein (hs-CRP) with the odds of cognitive impairment as well as its subtypes based on the Asymptomatic Polyvascular Abnormalities Community (APAC) study in China. Materials and methods: We conducted a cross-sectional analysis of the follow-up data of 2012 from the APAC study. The Chinese version of the MMSE was used as a cognitive screener, and an MMSE score <24 is generally accepted as indicating cognitive impairment. Multivariable logistic regression was used to estimate the interactions of hs-CRP levels with body mass index (BMI) on the effects of cognitive impairment and its subtypes. Results: Three thousand eight hundred seventy-five participants aged 40–90 years (median age 51.64 y) were enrolled in this study, and 1,788 (46.1%) were overweight. Before and after adjusting for confounders, such as age, sex, BMI, education, current smoking, drinking, physical activity, hypertension, hyperlipidemia, diabetes, and hs-CRP, elevated hs-CRP levels were associated with cognitive impairment in normal-weight participants (crude OR: 2.08, 95%CI: 1.28–3.37, p = 0.003; adjusted OR: 2.06, 95%CI: 1.03–4.10, p = 0.04), but not in overweight participants. There was no statistically significant evidence for the interaction between hs-CRP and BMI on any cognitive sub-item. Conclusion: Elevated hs-CRP levels increase the odds of cognitive impairment in normal-weight participants, but not in overweight participants.